Trees, terraces and llamas: Resilient watershed management and sustainable agriculture the Inca way - Frogley, M.R.; Chepstow-Lusty, A.; Thiele, G.; Chutas, C.A. (2025)
The Inca and their immediate predecessors provide an exceptional model of how to create high-altitude functional environments that sustainably feed people with a diversity of crops, whilst mitigating erosion, protecting forestry and maintaining soil fertility without the need for large-scale burning. A comparison is provided here of landscape practices and impacts prior to and after the Inca, derived from a unique 4200-year sedimentary record recovered from Laguna Marcacocha, a small, environmentally sensitive lake located at the heart of the Inca Empire. By examining ten selected proxies of environmental change, a rare window is opened on the past, helping to reveal how resilient watershed management and sustainable, climate-smart agriculture were achieved. We contend that, in the face of modern environmental uncertainty, a second climate-smart agricultural revolution is necessary, but one that accounts for the significant social capital of highland communities whilst still leaning heavily on native crops, trees and livestock.